Perancangan Asrama Mahasiswa UIN Ar-Raniry Banda Aceh - Zuhrahmi DE; Zulyaden Zulyaden; Mahmudin Marbun; Aminah Aminah; Merlisa Rahmi (Universitas Pahlawan Tuanku Tambusai, 2023)
Ar-Raniry State Islamic University is one of the universities located in Banda Aceh, Aceh, Indonesia. A student dormitory is a residential building dedicated to a homogeneous group. Currently, Ar-Raniry State Islamic University has not provided dormitories for underprivileged students who come from outside Banda Aceh and outside Aceh Province. Judging from the expensive rent of boarding houses or houses and the number of students who increase every year, this case can be concerning for underprivileged students. From the results of interviews with one hundred UIN Ar-Raniry students, student interest in the idea of building student dormitories is very large. As many as 90% of respondents strongly agreed and were even willing to live in the dormitory. The design of this student dormitory aims to ease the burden of underprivileged students and has benefits for building users. By applying a green architecture approach, the building is able to minimize adverse effects on the environment and the surrounding nature and is able to minimize the use of electricity by applying the principles of green architecture. Keywords: Dormitory, UIN Ar-Raniry, Green Architecture